FRI0676 A proposal for a simple ultrasound method for the diagnosis of early rheumatoid arthritis. (15th June 2017) - Serban, T; Satulu, I; Vutcanu, O; Milicescu, M; Mihai, CM; Bojinca, M
Abstract : Background: At this point, the classification criteria for rheumatoid arthritis (RA) are well known and generally applied in clinical practice. (1) Ultrasound (US) assessment can help in distinguishing the patients with early RA (ERA) within the patients with early inflammatory arthritis (EIA). Objectives: The aim of this study was to develop an US method for the diagnosis of ERA in a population of EIA patients from an Early Arthritis Research Center (EARC). Methods: We have assessed all patients with EIA referred to our EARC between 2012–2016. Patients who were diagnosed with other diseases except EIA or ERA, or in whom symptom duration exceeded 12 months, were excluded from the analysis. Every patient underwent clinical, laboratory and ultrasound evaluation. For the proposed US diagnostic method we have evaluated bilaterally 3 joints: wrists, MCP II and III and 2 tendon regions: the extensor ulnaris carpis tendon and the flexor tendons of the fingers. The presence/absence of synovitis/tenosynovitis either in gray-scale or power-Doppler scale was scored in a binary mode as 1/0. In order to simplify the scanning protocol, we considered the flexor tendons of the fingers as a singular structure for each hand which meant that that the presence of US abnormalities in at least one flexor tendon was scored as 1. Thus, the maximum score obtainable in both hands was 10. We analyzed the performance of the proposed US method for the diagnosis of ERA using ROC curve analysis. Results: Of 253 patients referred to our EARC, 73 satisfied the inclusion criteria; among them, 43 fulfilled the EULAR/ACR criteria for RA (ERA patients), while the other 30 were considered to have undifferentiated EIA. The demographic, clinical and US data of the 73 patients are displayed in the table below. 34/43 ERA patients (76.7%) had a duration of symptoms less or equal to 3 months which classifies them as very ERA (VERA). In ROC analysis, a cut-off of the US score of 4 had best results for sensitivity and specificity (73.3% and 82.1%, respectively), with an area under the curve of 0.812. The US score correlated with the levels of RF, ACPA, DAS28 and SDAI (p<0.001), but not with those of acute phase reactants (p>0.05). The time needed for performing the ultrasound examination was less than 10 minutes. Conclusions: The proposed US method proves to be reliable in identifying patients with ERA. The binary mode of US evaluation allows even persons with little training in US examination to diagnose patients. As the costs and time needed for US evaluation are low, the method is valuable in clinical practice for a rapid assessment of patients with EIA. References: Aletaha D et al. Arhritis Rheum. 2010;62:2569–258. Disclosure of Interest: None declared